Efektivitas Penegakan Hukum Undang-Undang Nomor 35 Tahun 2009 Oleh Kepolisian Resort Mandailing Natal. - Adi Syaputra Sirait, Indah Agustina & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
This type of research is a qualitative empirical juridical research. In empirical juridical research, it describes how the law operates in society. This research requires knowing about legal science, and having knowledge and social science (social science research). This research uses interview and observation methods. This study found the results that the effectiveness of Law no. 35 of 2009 concerning Narcotics Abuse (Adolescent Study in Panyabungan II Subdistrict, VI Environment, Panyabungan Subdistrict, Mandailing Natal District, to be precise in Environment VI, has not been carried out properly because there are more factors that abuse narcotics. In Law No. using Narcotics without rights or against the law. And the factors that occur in the abuse of narcotics by adolescents in Panyabungan Lingkungan VI Village, Panyabungan District, Mandailing Natal Regency are Environmental Factors, Lack of Parental Control, Social Media Influence, Economic Factors, and Lack of Understanding Religion.